Biodiversity, Climate Change, and Adaptation : Nature-based Solutions from the World Bank Portfolio - World Bank (World Bank, Washington, DC, 2012)
Climate change is a serious environmental challenge that could undermine the drive for sustainable development. Since the industrial revolution, the mean surface temperature of earth has increased an average of 1degree celsius per century due to the accumulation of greenhouse gases in the atmosphere. Furthermore, most of this change has occurred in the past 30 to 40 years, and the rate of increase is accelerating, with significant impacts both at a global scale and at local and regional levels. While it remains important to reduce greenhouse gas emissions and reverse climate change in the long run, many of the impacts of climate change are already in evidence. As a result, governments, communities, and civil society are increasingly concerned with anticipating the future effects of climate change while searching for strategies to mitigate, and adapt to, it's current effects.